2017
DOI: 10.1155/2017/2012798
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function and Mitophagy in the Elderly: Effects of Exercise

Abstract: Aging is a natural, multifactorial and multiorganic phenomenon wherein there are gradual physiological and pathological changes over time. Aging has been associated with a decrease of autophagy capacity and mitochondrial functions, such as biogenesis, dynamics, and mitophagy. These processes are essential for the maintenance of mitochondrial structural integrity and, therefore, for cell life, since mitochondrial dysfunction leads to an impairment of energy metabolism and increased production of reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 89 publications
(224 reference statements)
3
86
0
1
Order By: Relevance
“…Its beneficial effects on adults’ health has been related also to the induction of autophagy. Recent findings indeed suggested that exercise can induce autophagy in several tissues (e.g., adipose tissue and SkM) and organs (e.g., pancreas, liver, heart, and brain), supporting the evidence that exercise-mediated induction of autophagy could occur at systemic level [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 70%
“…Its beneficial effects on adults’ health has been related also to the induction of autophagy. Recent findings indeed suggested that exercise can induce autophagy in several tissues (e.g., adipose tissue and SkM) and organs (e.g., pancreas, liver, heart, and brain), supporting the evidence that exercise-mediated induction of autophagy could occur at systemic level [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 70%
“…Beneficial effects of caloric restriction (CR) in aging retardation have been observed in yeast, flies, worms, mice as well as non-human primates, and recent studies suggest that autophagy is required for lifespan extension by CR in multiple model organisms [ 3 , 211 , 212 , 213 ]. Interestingly, the health benefits of physical exercise partially overlap with CR in terms of improving cellular metabolism, increasing NAD + availability that activates sirtuins, stimulating PGC1α expression, and facilitating mitochondrial quality control [ 214 , 215 , 216 ]. Finally, pharmacological drugs such as rapamycin (mTOR inhibitor) and metformin (AMPK activator) also extend lifespan in model organisms and confer protection against several age-related pathologies [ 217 , 218 ].…”
Section: Mitochondria Aging and Age-associated Pathologiesmentioning
confidence: 99%
“…Mitochondrial remodelling can be conceptualized as a balancing act combining the generation of mitochondria with their dynamic modifications in the network (called fusion/fission), and subsequent clearance through macroautophagy (referred to as mitophagy) . Fusion facilitates ATP synthesis, prevents mitochondrial DNA loss and allows mingling of the organelles .…”
Section: Introductionmentioning
confidence: 99%
“…While numerous human interventional studies have confirmed the effect of exercise training on key regulators of mitochondria biogenesis in multiple populations, few have explored this effect in fusion and fission, with contradictory results, and none have looked at the effect of an exercise intervention on human muscle mitophagy. The primary aim of this study was to investigate in older adults, markers of mitophagy, fusion and fission using the exact same exercise intervention that increased mitochondrial content and efficiency in human skeletal muscle, focusing on internal validity and using a comprehensive picture of mitochondrial biology from the molecular level to the whole‐body level.…”
Section: Introductionmentioning
confidence: 99%